1969
DOI: 10.1203/00006450-196901000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fetal Exchange Transfusions with Adult Blood upon Fetal Oxygenation

Abstract: ExtractIntrauterine exchange transfusions were conducted i n fetal sheep using a d u l t sheep a s donors. I ndwelling catheters i n t h e fetus permitted sampling of blood for 8 to 36 days following t h e transfusion.I n t h e first days after t h e procedure there was a decreased oxygen affinity of umbilical blood, a n increase of a b o u t 5 mm Hg i n umbilical venous 0, tension, and a decrease of a b o u t 30 % in 0, saturation. I n t h e following weeks there was a g r a d u a l r e t u r n of 0, a f i n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

1971
1971
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 5 publications
1
3
0
1
Order By: Relevance
“…At a Pao" of 21 mm Hg, the arterial blood is 66% saturated in utero but only 36% saturated during bypass. Battaglia et al [1969] report a similar trend for umbilical venous saturation after a fetal exchange transfusion using adult red blood cells. The reduced hematocrit and the shift of the Oa dissociation curve, could reduce the oxygen content of the arterial blood by over 50%, even though the blood is maintained at an appropriate Pao._, of 21 mm Hg.…”
Section: Historical Developmentsupporting
confidence: 54%
“…At a Pao" of 21 mm Hg, the arterial blood is 66% saturated in utero but only 36% saturated during bypass. Battaglia et al [1969] report a similar trend for umbilical venous saturation after a fetal exchange transfusion using adult red blood cells. The reduced hematocrit and the shift of the Oa dissociation curve, could reduce the oxygen content of the arterial blood by over 50%, even though the blood is maintained at an appropriate Pao._, of 21 mm Hg.…”
Section: Historical Developmentsupporting
confidence: 54%
“…16 Experiments in sheep showed that exchange transfusion in sheep fetuses using adult sheep blood resulted in an overall decrease in oxygen affinity and saturation and, interestingly in view of our results, an increased reticulocytosis, whereas hemoglobin levels remained constant. 17 Adult hemoglobin is, however, also known to provide better peripheral tissue oxygenation compared with fetal hemoglobin, 16 which may result in a local reduction of hypoxic stimulus, causing reduced EPO production, which might explain the observed drastic decline in reticulocytes. In our institute, fetal EPO levels are not routinely measured.…”
Section: Discussionmentioning
confidence: 99%
“…One difference of major importance is in the oxygen dissociation characteristics of fetal cells which may be more closely related to the presence of a fetal membrane than fetal homoglobin [22]. Although adult cells transfused into the fetus may acquire some lipid characteristics of fetal cells [17], they retain an adult dissociation curve [4]. It would appear unlikely that this characteristic of fetal membrane is directly dependent on structural lipids which are susceptible to alteration by the plasma environment as previously postulated [7,16].…”
Section: Discussionmentioning
confidence: 86%